2020
DOI: 10.48550/arxiv.2012.05287
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A note on simplicial cliques

Maria Chudnovsky,
Alex Scott,
Paul Seymour
et al.

Abstract: Motivated by an application in condensed matter physics and quantum information theory, we prove that every non-null even-hole-free claw-free graph has a simplicial clique, that is, a clique K such that for every vertex v ∈ K, the set of neighbours of v outside of K is a clique. In fact, we prove the existence of a simplicial clique in a more general class of graphs defined by forbidden induced subgraphs.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…A graph G is said to be (even-hole, claw)-free, or ECF, if it contains no even holes and no claws among its induced subgraphs (see It can be shown that all (even-hole, claw)-free graphs are simplicial, meaning they contain a simplicial clique [3]. If a Hamiltonian H is ECF then its frustration graph is necessarily simplicial, so we say that H is simplicial as well.…”
Section: Definition 3 (Ecf)mentioning
confidence: 99%
See 3 more Smart Citations
“…A graph G is said to be (even-hole, claw)-free, or ECF, if it contains no even holes and no claws among its induced subgraphs (see It can be shown that all (even-hole, claw)-free graphs are simplicial, meaning they contain a simplicial clique [3]. If a Hamiltonian H is ECF then its frustration graph is necessarily simplicial, so we say that H is simplicial as well.…”
Section: Definition 3 (Ecf)mentioning
confidence: 99%
“…It is therefore computationally efficient to recognize a simplicial clique in an ECF graph. Moreover, every (nonempty) ECF graph has at least one simplicial clique [3].…”
Section: Relation To Prior Workmentioning
confidence: 99%
See 2 more Smart Citations